Infrapatellar Fat Pad/Synovium Complex in Early-Stage Knee Osteoarthritis: Potential New Target and Source of Therapeutic Mesenchymal Stem/Stromal Cells - Greif, Dylan N.; Kouroupis, Dimitrios; Murdock, Christopher J.; Griswold, Anthony J.; Kaplan, Lee D.; Best, Thomas M.; Correa, Diego (Frontiers in Bioengineering and Biotechnology, 2020)
The Infrapatellar Fat Pad (IFP) has until recently been viewed as a densely vascular and innervated intracapsular/extrasynovial tissue with biomechanical roles in the anterior compartment of the knee. Over the last decade, secondary to the proposition that the IFP and synovium function as a single unit, its recognized tight molecular crosstalk with emerging roles in the pathophysiology of joint disease, and the characterization of immune-related resident cells with varying phenotypes (e.g., pro and anti-inflammatory macrophages), this structural complex has gained increasing attention as a potential therapeutic target in patients with various knee pathologies including osteoarthritis (KOA). Furthermore, the description of the presence of mesenchymal stem/stromal cells (MSC) as perivascular cells within the IFP (IFP-MSC), exhibiting immunomodulatory, anti-fibrotic and neutralizing activities over key local mediators, has promoted the IFP as an alternative source of MSC for cell-based therapy protocols. These complementary concepts have supported the growing notion of immune and inflammatory events participating in the pathogenesis of KOA, with the IFP/synovium complex engaging not only in amplifying local pathological responses, but also as a reservoir of potential therapeutic cell-based products. Consequently, the aim of this review is to outline the latest discoveries related with the IFP/synovium complex as both an active participant during KOA initiation and progression thus emerging as a potential target, and a source of therapeutic IFP-MSCs. Finally, we discuss how these notions may help the design of novel treatments for KOA through modulation of local cellular and molecular cascades that ultimately lead to joint destruction.